Optimizing Number of Fertilizing Employees Based On Work Time at PT.Tanjung Buyu Perkasa Plantation East Kalimantan - Suhendra, Ade; Bulkis, Sofyan; Thamrin, Herijanto; M Atta, Bary; Supriono; Purwanto, Dody; Mulyadi, Fadli (Politeknik Pertanian Negeri Samarinda, 2024)
Every company needs employees as human resources, which has an important role as human resources, employees are one of the main supporter in process of the plantation. Oil palm plantations have quite high development prospects, with a broad scope of plantations that require high adequate management and human resources. Based on research that has been done obtained the highest productive work time on fertilizer employees 4 is (54.1%) with the lowest productive time on fertilizer employees 2 is (32.2%), for the highest unproductive time on fertilizer employees 1 (34.1%) with the lowest non-productive time for fertilizer employees 1 (22.2%). While the lowest personal time was on fertilizer employees 4 (19.2%) and the highest was on fertilizer employees 2 (40.7%). The blocks have the highest productive time and lowest personal time because the terrain at turning is very heavy or hilly so that the task completion time is longer. The effective working day at the company is 289 days with working time / year 121,380 minutes, the total number of effective employee needs is 8 (eight) people with actual employees is 17 people, the solution to overcome the excess employee is to shift work to other jobs, improve performance in terms of starting a job on time. Keywords: workload analysis, employee needs, work sampling